1985
DOI: 10.1016/0014-5793(85)80718-3
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyridine Ca2+ agonists and channel blockers interact in the opposite manner with photogenerated unpaired electrons

Abstract: Interaction of Ca2+-channel antagonrsts (felodipmne, ryocrdil, verapamil, diltrazem) and agonists (dthydropyrrdtne derrvatives Bay K 8644 and CGP 28392) was studied by the methods of absorption spectroscopy Ca2+-channel antagonists were found to act as electron donors, the agonrsts being electron acceptors m the interaction with dye free radicals m solution Redox transitions m channel-forming protein were proposed as a possrble mechanism of the modulation of channel actrvity by the compounds tested

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It is not yet known whether a similar approach can be applied to other protein targets. Previous studies have shown that inhibitors of the L-type Ca 2ϩ channel (i.e., nifedipine, verapamil, and diltiazem) are electron donors (Marinov and Saxon, 1985), whereas local anesthetics, antiarrhythmic agents, and some anticonvulsants, which inhibit Na ϩ channels, are also electron donors (Marinov, 1985). In contrast, both K201 and its dioxole derivative, with enhanced electron donor properties, show similar potency for inhibiting ATPase activity of sarcoplasmic/endoplasmic reticulum Ca 2ϩ -ATPase type 1.…”
Section: Discussionmentioning
confidence: 99%
“…It is not yet known whether a similar approach can be applied to other protein targets. Previous studies have shown that inhibitors of the L-type Ca 2ϩ channel (i.e., nifedipine, verapamil, and diltiazem) are electron donors (Marinov and Saxon, 1985), whereas local anesthetics, antiarrhythmic agents, and some anticonvulsants, which inhibit Na ϩ channels, are also electron donors (Marinov, 1985). In contrast, both K201 and its dioxole derivative, with enhanced electron donor properties, show similar potency for inhibiting ATPase activity of sarcoplasmic/endoplasmic reticulum Ca 2ϩ -ATPase type 1.…”
Section: Discussionmentioning
confidence: 99%
“…The methods developed in this paper to assay for the electron donor versus acceptor properties of various CRC modulators are similar to those used in previous studies in which reagents that modify Na + and Ca 2+ channels were examined (17,20), and to a recent study in which ryanodine was shown to act as an electron acceptor using flash photolysis techniques (18). However, this is the first time these types of assays have been carried out in an aerobic environment.…”
Section: Redox Control Of Ryr 617mentioning
confidence: 92%
“…While thiol reagents chemically react with the RyR thiols producing a long-lasting effect, non-thiol channel modulators shift the SH/S-S balance in a reversible manner-their effects last only as long as they remain bound to the RyR. It is important to note that the proposed mechanism in which RyR activators are electron acceptors, and channel inhibitors are electron donors is not unique to the Ca 2+ release channel from SR. Inhibitors of the L-type Ca 2+ channel (nifedipine, verapamil, and diltiazem) have been shown to act as electron donors, while L-type channel activators such as Bay K 8644 acts as an electron acceptor (20). Local anesthetics, antiarrhythmics, and some anticonvulsants, which inhibit sodium channels, acted as electron donors in reactions with free radicals, while the sodium channel "agonists": veratridine, N-bromosuccinimide, and chloramine-T all behaved as electron acceptors, despite differences in chemical structures (17).…”
Section: Redox Control Of Ryr 619mentioning
confidence: 99%
“…Because of this property, they could affect any of the multiple cellular systems that have evidence of redox modulation. These include receptor activation (5-10), control of ion channels and pumps (11)(12)(13)(14)(15)(16)(17), G protein signaling (18)(19), and transcription factor activation (20). Although the concentrations used in this study are slightly higher than the 10 µM used when they are given as inhibitors (2)(3), it is known that these fatty acids are lipophilic and concentrate to much higher levels in membranes.…”
Section: Resultsmentioning
confidence: 93%